Effects of whole-body vibration training on explosive strength and postural control in young female athletes - Fort, A.; Romero, D.; Bagur, C.; Guerra, M. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to evaluate the effectiveness of a whole-body vibration training program to improve neuromuscular performance in young elite female athletes. Twenty-three women basketball players (14-18 years old) were randomly assigned to a control group (CG, n = 11) or to a whole-body vibration group (WBVG, n = 12). During the study period, both groups continued their usual training program, but the WBVG also underwent a 15-week vibration training program. We analyzed the countermovement jump test (CMJ), the 1-leg hop test for the right leg and for the left leg, and the single-limb standing balance for both legs and with eyes open and closed at 3 time points: before training (T1), after an 8-week training period (T2), and after a further 7-week training period (T3). Compared with the CG, CMJ increased significantly in the WBVG from T1 to T2 (6.47%, p < 0.001), T1 to T3 (10.07%, p = 0.005), and T2 to T3 (3.38%, p < 0.001). One-leg hop test for the right and left legs also showed significantly higher values in WBVG from T1 to T2 (10.12%, p < 0.001 and 9.63%, p = 0.002, respectively) and T1 to T3 (14.17%, p = 0.001 and 15.17%, p = 0.004, respectively). Lateral deviation of the center of pressure in the closed eyes test decreased significantly in WBVG for both right and left leg, from T1 to T2 (-22.20%, p = 0.043 and -34.77%, p < 0.001, respectively) and from T1 to T3 (-33.14%, p = 0.027 and -33.58%, p = 0.043, respectively) compared with the CG. In conclusion, our results show that a 15-week whole-body vibration training program improves explosive strength and postural stability in adolescent female basketball players.